COMMUNICATION AND INTERNATIONAL LANGUAGE - Aisyah Pratiwi (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
English as an international language is widely spoken by many people around the world. There are billions of people who use English as their first, second, and foreign language. This library research aims to discover the importance of English as an International Language (EIL) in global communication and broadcasting. Using recent statistical data, theory, and journals, the researcher seekS the information on the importance of EIL for communication and broadcasting field. Those instruments are fully described qualitatively. As the result, the researcher found that the relationship of English proficiency with the communication and broadcasting field is inevitable. Using English, obtaining, sharing, and spreading information, ideas, and opinions will be easier and reach many more people as the main purpose of communicating and broadcasting.